AVALIAÇÃO ANTROPOMÉTRICA DE IDOSOS ATENDIDOS NO AMBULATÓRIO DE NUTRIÇÃO DO CENTRO DE REFERÊNCIA EM ASSISTÊNCIA À SAÚDE DO IDOSO DA UNIVERSIDADE FEDERAL FLUMINENSE, NO MUNICÍPIO DE NITERÓI-RJ - Ana Luiza Sant'Anna da Costa Silva; Beatriz dos Santos da Silva; Joana Maia Brandão; Sergio Girão Barroso; Gabrielle de Souza Rocha (Universidade do Estado do Rio de Janeiro, 2015)
Objective: To describe the body and anthropometric compositionof the elderly assisted in the Nutrition Clinic of the ReferenceHealthcare Center for the Elderly, Universidade Federal Fluminense,Niteroi city, Brazil. Methodology: This is a cross-sectional studywith 52 subjects aged 60 years or older treated at the nutritionclinic. Anthropometric measurements were performed accordingto the guidelines of the International Society for the Advancementof Kineanthropometry considering the following variables: bodyweight, height, biceps, triceps, subscapular, supra-iliac skinfoldthicknesses, body fat percentage based on the sum of the fourskinfolds, waist circumference and arm circumference. Statisticalanalyzes were performed using Graph Pad Instat® software,version 3.1, considering p <0.05 as significant value. Results:There was prevalence of overweight (43.5% of the sample),adequacy of the arm circumference, arm muscle circumferenceand triceps skinfold. Most women (67.6%) had high risk forcardiovascular disease according to waist circumference. Therewas high percentage of body fat in both sexes (89.2% and 66.7%in female and male, respectively). Conclusion: We observedthe presence of inadequacies of the nutritional status of thepopulation under study according to anthropometric parameters- body mass index, waist circumference, and percent of body fatbased on the skinfold sum. DOI: 10.12957/demetra.2015.15949